2019
DOI: 10.1002/jcop.22237
|View full text |Cite
|
Sign up to set email alerts
|

A promising recovery housing model for American Indian communities

Abstract: In 2016, two Oxford House (OH) recovery homes were established for the Suquamish Tribal reservation. A group of researchers interviewed house members and key individuals responsible for the creation of these two unique OHs. Because American Indians are an at-risk population for substance use disorders, our study explored whether an OH-type recovery home model could be successfully adapted to this population, given the specific nature of tribal cultures. Findings indicated that the residents, composed of both A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Sixty percent of the studies reported Reach [ n = 12; ( 33 , 35–38 , 40 , 42 , 45–48 , 50 )] with information mainly focused on inclusion and exclusion criteria for participants along with recruitment strategies ( 33 , 35 , 36 , 40 , 42 , 45 , 46 , 48 , 50 ). For example, Campbell and colleagues ( 35 ) noted that they recruited 58.8% ( N = 40) out of the 68 clients that were eligible to participate in their study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sixty percent of the studies reported Reach [ n = 12; ( 33 , 35–38 , 40 , 42 , 45–48 , 50 )] with information mainly focused on inclusion and exclusion criteria for participants along with recruitment strategies ( 33 , 35 , 36 , 40 , 42 , 45 , 46 , 48 , 50 ). For example, Campbell and colleagues ( 35 ) noted that they recruited 58.8% ( N = 40) out of the 68 clients that were eligible to participate in their study.…”
Section: Resultsmentioning
confidence: 99%
“…Making cultural adaptations to evidence-based substance use disorder treatment was described as a more holistic approach that sits within the cultural framework of the partnering community. This can take the form of integrating appropriate representation (e.g., art, study staff from the community) knowledge, and Indigenous worldviews into the evidence-based treatment which may also increase engagement and adoption ( 33 , 42 , 43 , 50 ) ( Table 1 ). Seventy-five percent of the studies ( n = 15) mentioned culturally adapting the intervention, but only 15.0% ( n = 3) described a specific framework guiding the adaptations made.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 The effectiveness of the approaches taken by Native nations and Indigenous community health (ICH) organizations is attributed to customary relationships between tribal leaders and citizens and engagement as rightsholders in partnerships with non-tribal and governmental entities. [1][2][3][4][5][6][7][8][9][10] With direct funding, Native nations and ICH organizations can continue to build upon this evidence, tackle structural barriers, and further their engagement in systems and implementation science research. This commentary shares evidence that demonstrates how direct funding can enhance Native nations and Indigenous community (NNIC) driven research using Indigenous systems alignment frameworks and improve long-term collaboration with internal and external, cross-sector partners (e.g., tribal government divisions, nonprofit community health clinics, etc.…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of the approaches taken by Native nations and Indigenous community health (ICH) organizations is attributed to customary relationships between tribal leaders and citizens and engagement as rightsholders in partnerships with non‐tribal and governmental entities 1–10 . With direct funding, Native nations and ICH organizations can continue to build upon this evidence, tackle structural barriers, and further their engagement in systems and implementation science research.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation